Re-launching the bi-regional dialogue between the EU and Latin America: Simple revival or fundamental renewal? - Günther Maihold; Claudia Zilla (Stiftung Wissenschaft und Politik (SWP), 2023)
The summit in Brussels on 17-18 July will mark the end of a long eight-year hiatus in bi‑regional meetings between the European Union (EU) and the Community of Latin American and Caribbean States (CELAC). Between 1999 and 2015, conferences were held every two or three years. Since the last conference, the international environment and regional contexts on both sides of the Atlantic have changed significantly. Brazil's return to CELAC and the new Lula government's efforts to reactivate the Union of South American Nations (UNASUR) have given the region a new impetus, which was reflected at the respective summits of the two organisations in Buenos Aires in January and Brasília in May. In June, the European Commission presented a new agenda for the EU's relations with Latin America and the Caribbean (LAC) that clearly shows Europe wants to intensify bi-regional cooperation. This has a chance of succeeding if summit diplomacy is approached in a spirit of renewal - not revival - and combined with substantive thematic cooperation and vibrant bilateral relations.
Keywords: 320; European Union (EU); Community of Latin American and Caribbean States (CELAC); Union of South American Nations (UNASUR); Latin America and the Caribbean (LAC)